Experimental study on cyclic shear behavior of biopolymer-treated soil as a tunnel backfill material - Park, D. Y.; Lee, M. H.; Cho, G. C.; Chang, I. H. (Expanding Underground - Knowledge and Passion to Make a Positive Impact on the World- Proceedings of the ITA-AITES World Tunnel Congress, WTC 2023, 2023)
The purpose of backfill grout injection is to immediately fill voids left by the TBM body between the tunnel wall and the segmented blocks, preventing subsidence in the surrounding ground structure. The backfill material must resist various shear behaviors during tunnel operation. When cement is used as the primary material for grout, two significant problems can occur. First, the cement-based material has a small damping ratio. Therefore, stability against dynamic loading is low. Second, cement causes serious environmental problems because it causes alkalization due to its direct contact with the ground. Biopolymer-soil treatment improves strength and stiffness and has injection capabilities and permeability reduction effects, showing potential as a tunnel grouting material. However, the performance related to dynamic load has not been evaluated much. Therefore, applying biopolymer-based backfill grouting material will be evaluated through cyclic direct simple shear test by acquiring various types of geotechnical properties of the biopolymer-treated soil.
Keywords: Backfill material; Cyclic shear; Ground structure; Grout injection; Grouting materials; Primary materials; Shear behaviour; Treated soils; Tunnel operation; Tunnel wall